Perubahan Pengelolaan Pembelajaran di Lembaga Pendidikan Tingkat Dasar Pada Masa Pandemi Covid-19; Studi di Madrasah Ibtidaiyah (MI) dan Sekolah Dasar (SD) Swasta Kabupaten Mojokerto - Syaikhu Rozi; Muhammad Ali Rohmad (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
This research was conducted to analyze the forms of changes in the management of learning of basic education institutions in Mojokerto Regency in the Covid-19 pandemic and their backgrounds. The research is carried out qualitatively with a double case study approach. Based on the results of the study can conclude that the situation and conditions of the Covid-19 pandemic have changed the management of learning at MI Hidayatul Mubtadi'in and in Nurul Islam Elementary School, which was originally implemented face-to-face in classrooms, turned into online learning. At MI Hidayatul Mubtadi'in, online learning is carried out for key subjects. As for face-to-face learning directly still carried out for the learning of the Qur'an and the development of morals and ubudiyah activities because it cannot be replaced with other learning such as online learning and the like. Meanwhile, in Nurul Islam Elementary School, learning using semi-online and semi-offline systems is carried out for the learning of major subjects. As for the learning of the Qur'an and ubudiyah-yaumiyah activities are not carried out systematically in school. But it is only done simply by handing over more management to the parents of students.